Impulsivity, aggression and trauma history in repeat and one-off female offenders. - Braham, Lydia (2019)
The aim on this study was to investigate self-reported impulsivity, aggression and trauma history in repeat and one-off female offenders. This research was deemed necessary, due to the small amount of knowledge surrounding female offending behaviour and repeat offending. Female service users recruited at Together Women Project Leeds, Bradford and Sheffield (n=22) completed the Barratt Impulsivity Scale, Aggression Questionnaire and International Trauma Questionnaire presented in a paper format. Participants were grouped by number of convictions, one conviction or more than one. Previous research indicates that females with more than one conviction will score higher on each scale than those with one conviction. A t-test and Mann-Whitney U test found that whilst overall, those with more than one conviction obtained higher means than those with one conviction, only significant results were found in physical aggression and attentional impulsivity sub scales. This research was not without its limitations however, finding the sample difficult to access resulting in a low sample size, as well as low literacy skills effecting participation.